Normal opening pressure lumbar puncture in cryptococcal meningitis complicated by a cerebral venous thrombosis: a case report and literature review - Tee, Vincent; Maiden, Abdul Hakim; Othman, Fatimah; Chua, Ping Sheng; Wong, Mung Seong (Frontiers in Medicine, 2025)
Cryptococcal meningitis (CM) is a severe fungal infection that primarily affects individuals with compromised immune systems, such as those living with HIV/AIDS or undergoing immunosuppressive therapy. Elevated intracranial pressure is a common complication of CM and remains an important diagnostic parameter in patients with CM. This report describes a case of CM complicated with cerebral venous thrombosis (CVT) in an immunocompetent patient residing in the southern region of Peninsular Malaysia. The diagnosis of CM was confirmed by cerebrospinal fluid (CSF) culture; however, the patient presented with normal opening pressure during lumbar puncture. The pathophysiology and factors of causality, together with their diagnostic challenges, are discussed.